6 - ‘From Cradle to Grave’: Transforming South Africa’s Learning Ecologies - Monyooe, Lebusa (Journal of Higher Education in Africa, 2022)
This article examines key organizational principles that underpin responsive transformation strategies that have the potential to create spaces for critical engagement with South Africa’s basic education post the 1994 democratic elections. The article deploys various metaphors like the ‘ants, ecology, London Tube and bridge construction’ to unravel the deeper elements for transforming schools into sustainable learning ecologies. It concludes with an articulation of plausible interventions that the country may deploy to improve educational quality and the system’s efficacy.